Graphenylene, a unique two-dimensional carbon network with nondelocalized cyclohexatriene units - Song, Q.; Wang, B.; Deng, K.; Feng, X.; Wagner, M.; Gale, Julian; Mullen, K.; Zhi, L. (RSC Publishing, 2013)
Over many years chemists have established the general principle that two-dimensional chemical structures constructed with pure sp2-carbon atoms will definitely form an aromatic system with delocalized electron density. However, based on a recently proposed chemical structure, graphenylene, this rule may finally be broken. Herein, we predict the properties of a new two-dimensional sp2- carbon network known as graphenylene, which is the first example of a non-delocalized sp2-carbon structure composed of cyclohexatriene units with two quite distinct C–C bonds within a C6 ring. In addition, theoretical calculations demonstrate that graphenylene has periodic pores of 3.2 Å in diameter and is a semiconductor with a narrow direct band gap, making it promising for various applications, such as electronic devices and efficient hydrogen separation. This study provides a new perspective on carbon allotropes, leading to a better understanding of [N]phenylene based organic frameworks, as well as clarifying the relationship between benzene and cyclohexatriene.